(untitled) (Journal of Global Accounting, 2025)
The study examined the moderating role of information and communication technology on the relationship between corporate governance and fraud detection in listed deposit money banks in Nigeria. Corporate governance was proxied using board competence (BODC), board diversity (BODD) and board independence (BODIND); fraud detection on the other hand was measured using Beneish M-Score Model while the moderating variable of information and communication technology (ICT) was proxied using information and communication technology expenditure (ICTE). Ex post facto research design was adopted and the data for the study was collected from the annual reports and accounts of the 14 listed deposit money banks on Nigeria Exchange Group (NGX) as of December 31, 2024 for the period of 2019-2024. Panel Least squares regression model was used in the data analysis and the results of the study showed a significant and positive association between board competence (BODC), board diversity (BODD), board independence (BODIND) and fraud detection in listed deposit money banks in Nigeria at 1%-5% significant level. Information and communication technology (ICT) was also found to moderate the relationship between corporate governance and fraud detection at 1%-5% level of significance. The study therefore concludes that corporate governance enables fraud detection in listed deposit money banks in Nigeria. Also, ICT moderated the relationship between corporate governance and fraud detection. The study therefore recommends that banks should prioritize the recruitment of highly competent individuals for their boards so as to enable fraud detection in listed deposit money banks in Nigeria. Ensuring diversity across gender could deter the likelihood of fraud commitment in listed deposit money banks in Nigeria. Also, DMBs are encouraged to increase the number of their independent directors in order to reduce the likelihood of fraud commitment.